Unveiling leadership dynamics and tournament incentives: insights from the environmental misconduct of Chinese listed companies - Khan, Farman Ullah; Trifan, Vanina Adoriana; Zhang, Junrui; Sinaci, Maria; Blaga, Radu Lucian (Journal of Business Economics and Management, 2025)
This study investigates whether the tournament compensation motivate executives to adopt environmentally responsible practices and reduce environmental violations. Focusing on CEO characteristics, we also examine whether politically connected CEOs and CEO gender enhance the effectiveness of these incentives in mitigating corporate environmental violations. Using a fixed-effects model, two stage least square (2-SLS) and the Generalized Method of Moments (GMM) on data from Chinese companies, spanning from 2010 to 2023, this study finds that executive tournament incentives play a significant role in reducing environmental violations. Our results further reveal that political connections and female CEOs strengthen the negative relationship between tournament incentives and environmental violations, demonstrating the critical influence of leadership diversity and institutional ties in driving corporate sustainability. Additionally, our findings provide robust support for tournament theory, highlighting the pivotal role of CEOs in shaping corporate environmental behaviour. This study provides pertinent insights for regulators and policymakers, assisting them to develop tailored strategies, regulations and legislative frameworks to reduce environmental violations and improve sustainable development.